Mass production of Tiger Grouper, Epinephelus Fuscoguttatus through hatchery and grow-out systems - Yukinori Mukai; Shigeharu Senoo (Universiti Malaysia Sabah, 2004)
This study was performed to get basic knowledge of egg collection on tiger grouper, Epinephelus fuscoguttatus through natural spawning in a 150-ton broodfish tank. The chosen E. fuscoguttatus were transferred from the net cage into the broodfish tank. Water quality (temperature, dissolved oxygen, pH and salinity) was measured twice per day and the E. fuscoguttatus were fed with trash fish. An egg net was set up in the broodfish tank every month to collect the eggs of E. fuscoguttatus. Approximately 105 million eggs were collected from May 2004 until November 2004. Spawning occurred in July (46 million eggs), August (24 million eggs) and October (35 million eggs) 2004. There was an obvious relationship between their spawning rhythm and the lunar cycle. The biggest egg diameter (0.880 mm ± 0.018 mm) (mean ± S.D.) and the highest fertilization rate (95.2% ± 5.7%) were considered the best egg quality. On the other hand, from the water parameter results, spawning could occur at 27.6°C, dissolved oxygen 6.52 mgL-1, salinity 31.5 ppt and pH 7.94 on average. A biotelemetry experiment on E. fuscoguttatus was conducted to measure the fish body temperature and the depth, where the fish stayed in the broodfish tank. Data loggers were able to record the temperature and water depth at 2-minute intervals continuously for 30 days. Data loggers were inserted into the abdomen of a female and a male. On average, the female swam between 1.2 times/night and 3.8 times/night to the water surface during the spawning periods. However, it was only 0.6 times/night during the non-spawning periods. From this study, the 150-ton broodfish tank with 3 m depth is suitable for the egg collection of E. fuscoguttatus through natural spawning. This broodfish tank system can be introduced to other hatcheries in order to get a constant supply of E. fuscoguttatus eggs.